Proposing a training program based on the cardio training method using short-duration weight exercises (SDWE) and its impact on some anthropometric variables (weight, body mass index) among some trainees in fitness halls. - لعيدي , عبد الرحيم (Journal of Sport Science Technology and Physical Activities, 2024)
The study aimed to determine the effect of the proposed training program using the (Cardio) training method using short-duration weight exercises (SDWE) on some anthropometric variables among some trainees who suffer from obesity. The researcher used the experimental method, and the study sample included 10 trainees who were chosen intentionally. After collecting the results and processing them statistically, the study showed that there were statistical differences in the results of the pre- and post-tests of the sample members. The study recommended using this method with trainees looking to lose weight